2023
DOI: 10.3389/fimmu.2023.1142609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunotherapy and chemotherapy-related molecular subtypes in colon cancer by integrated multi-omics data analysis

Abstract: BackgroundColon cancer is a highly heterogeneous disease, and identifying molecular subtypes can provide insights into deregulated pathways within tumor subsets, which may lead to personalized treatment options. However, most prognostic models are based on single-pathway genes.MethodsIn this study, we aimed to identify three clinically relevant subtypes of colon cancer based on multiple signaling pathways-related genes. Integrative multi-omics analysis was used to explain the biological processes contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, researchers have discovered an association between the mRNA-based expression subtypes and ICI response, while the Tumor Mutational Burden (TMB) status and transcriptome expressions can be used to guide treatment choices using platform L1000. Also, they created a classifier that can help identify the best drug for a colon cancer patient based on their gene expression [ 19 ].…”
Section: Dissecting the Tme With Multi-omics Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, researchers have discovered an association between the mRNA-based expression subtypes and ICI response, while the Tumor Mutational Burden (TMB) status and transcriptome expressions can be used to guide treatment choices using platform L1000. Also, they created a classifier that can help identify the best drug for a colon cancer patient based on their gene expression [ 19 ].…”
Section: Dissecting the Tme With Multi-omics Approachmentioning
confidence: 99%
“…Furthermore, the TCIA database (https://tcia.at/home, accessed on 18 March 2024) provides immunotherapy prediction information based on comprehensive immunogenomic analyses of next-generation sequencing data (NGS) of 20 types of cancer, including breast cancer. This information can be used to predict the immune checkpoint inhibitor (ICI) response of patients with distinct subtypes of breast cancer [19].…”
Section: Immunotherapy and Biomarkers: The New Perspectivementioning
confidence: 99%
“…The gene expression subtypes of COAD and COADREAD were proposed by the Cancer Genome Atlas (TCGA) research network respectively 9 , 10 . A recent study also identified molecular subtypes of colon cancer based on multiple platforms, including molecular subtypes of COAD patients 11 , and several molecular subtypes of colon cancer based on different gene sets 12 . However, early colon cancer has some special molecular characteristics, and in these subtypes and gene sets, the prognostic information of patients is not well used, resulting in weak prognostic ability of patients.…”
Section: Introductionmentioning
confidence: 99%
“…First, it can inhibit tumorigenesis by blocking upstream signaling pathways. This includes ligand-neutralizing antibodies, decoy receptors or inhibitors that block TGFβ, NF-κB, EGFR, cMET, WNT and Notch signals 12 34 . In addition, effective inducers of EMT include a variety of proinflammatory signals, such as TNF-α 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, CRC is considered the most common type of cancer in men and the third most common cancer type among women [ 3 ]. The development of CRC was related to multiple signaling pathways, including the cell cycle, immunity, aging, and metabolism [ 4 ]. Generally, the treatment of CRC depends on the stage of the tumor.…”
Section: Introductionmentioning
confidence: 99%